Chapter 9 Prosodies of affect and emotional climates - Tait, Peta (Taylor & Francis, 2022)
"Forms of Emotion analyses how drama, theatre and contemporary performance present emotion and its human and nonhuman diversity. This book explores the emotions, emotional feelings, mood, and affect, which make up a spectrum of 'emotion', to illuminate theatrical knowledge and practice and reflect the distinctions and debates in philosophy, neuroscience, psychology, and other disciplines. This study asserts that specific forms of emotion are intentionally unified in drama, theatre, and performance to convey meaning, counteract separation and subversively champion emotional freedom. The book progressively shows that the dramatic and theatrical representation of the nonhuman reveals how human dominance is offset by emotional connection with birds, animals, and the natural environment. This book will be of great interest to students and researchers interested in the emotions and affect in dramatic literature, theatre studies, performance studies, psychology, and philosophy as well as artists working with emotionally expressive performance."